Delivery of Brief Cognitive Behavioral Therapy for Medically Ill Patients in Primary Care: A Pragmatic Randomized Clinical Trial - Cully, Jeffrey A. (J Gen Intern Med, 2017)
BACKGROUND: Few studies have examined the practical effectiveness and implementation potential of brief psychotherapies that integrate mental and physical health. OBJECTIVE: To determine whether an integrated brief cognitive behavioral therapy (bCBT), delivered by mental health providers in primary care, would improve depression, anxiety and quality of life for medically ill veterans. DESIGN: Pragmatic patient-randomized trial comparing bCBT to enhanced usual care (EUC). PARTICIPANTS: A total of 302 participants with heart failure and/or chronic obstructive pulmonary disease (COPD) with elevated symptoms of depression and/or anxiety were enrolled from two Veterans Health Administration primary care clinics. INTERVENTION: bCBT was delivered to 180 participants by staff mental health providers (n = 19). bCBT addressed physical and emotional health using a modular, skill-based approach. bCBT was delivered in person or by telephone over 4 months. Participants randomized to EUC (n = 122) received a mental health assessment documented in their medical record. MAIN MEASURES: Primary outcomes included depression (Patient Health Questionnaire) and anxiety (Beck Anxiety Inventory). Secondary outcomes included health-related quality of life. Assessments occurred at baseline, posttreatment (4 months), and 8- and 12-month follow-up. KEY RESULTS: Participants received, on average, 3.9 bCBT sessions with 63.3% completing treatment (4+ sessions). bCBT improved symptoms of depression (p = 0.004; effect size, d = 0.33) and anxiety (p < 0.001; d = 0.37) relative to EUC at posttreatment, with effects maintained at 8 and 12 months. Health-related quality of life improved posttreatment for bCBT participants with COPD but not for heart failure. Health-related quality of life outcomes were not maintained at 12 months. CONCLUSIONS: Integrated bCBT is acceptable to participants and providers, appears feasible for delivery in primary care settings and is effective for medically ill veterans with depression and anxiety. Improvements for both depression and anxiety were modest but persistent, and the impact on physical health outcomes was limited to shorter-term effects and COPD participants. Clinical trials.Gov identifier: NCT01149772